(3GdbHS aj TQM ehWC eGdc Hf CfSs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s; (3eGdc Hf CfS Hf eGdc GdCUHMj GdMejQj, CHh YHO Gddg,J (B179 (3g` s
(3ChdgG (B:s
(3gPG Chd cJGH Cda ai TQGFY GdESdGe hgh BNQg dCfg de jDda eKdg s
(3BNQgG (B:s
(3de jcf ddeQCI cdGe ai Pdc dCf GdRhL jaVdgG HGdbhGeI GfJgi s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ YfGhjfgG HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs